Optical and structural properties of individual Co-doped ZnO microwires. (June 2018) - Kolomys, O.F.; Strelchuk, V.V.; Rarata, S.V.; Hayn, R.; Savoyant, A.; Giovannelli, F.; Delorme, F.; Tkach, V.
Abstract: The Co-doped ZnO microwires (MWs) were grown using the optical furnace method. We used Scanning electron microscopy (SEM), polarized micro-Raman spectroscopy, photoluminescence (PL) and optical absorption spectroscopy to systematic investigation of the optical and structural properties of Co-doped ZnO MWs. The SEM analysis reveals that Co-doped ZnO MWs has hexagonal facets and cavity inside. The EDS results confirmed the presence and non-uniform distribution of Co impurities in the samples. Co doping of ZnO MWs leads to the decreased intensity, drastically broadening and high-energy shift of the NBE PL band. The red emission band at 1.85 eV originates from 2 E( 2 G) → 4 A2 ( 4 F) intra-3d-transition of Co 2+ in the ZnO lattice has been observed. The intense structured absorption bands within the near infrared ranges 3800–4800 and 5500–9000 cm −1 are caused by electronic spin-allowed transitions 4 T2 (F) ← 4 A2 (F) and 4 T1 (F) ← 4 A2 (F) of the tetrahedrally coordinated Co 2+ (3 d 7 ) ions substituting Zn 2+ ions in Co-doped ZnO MWs. Micro-Raman studies of Co doped ZnO MWs show doping/disorder induced additional modes as compared to the undoped sample. The resonant enhancement of the additional local Co-related A1 -symmetry Raman mode is observed in the parallel polarization geometry y ( z, z ) y ¯ . For the Co doped ZnO MWs, the enhancement of the additional Co-related local vibration mode with an increase in the excitation photon energy is also observed in the Raman spectra. Highlights: Cobalt-doped (0-2%) ZnO microwires with high crystallinity were grown by optical furnace method. Raman, FTIR, PL, and EDS methods confirmed presence of Cobalt ions in the ZnO microwires. The red emission at 1, 8 eV is related to the 2 E( 2 G) → 4 A2 ( 4 F) intra-3d-transition of Co 2+ ions in the ZnO lattice. The Co-related Raman mode at 552 cm -1 increases in intensity with Co content. Resonant enhancement of Co-related Raman mode is registered under subband excitation.